Stomal recurrence: Salvage surgery and reconstruction utilizing microvascular free tissue transfer. Issue 10 (18th December 2013) - Pittman, Amy; Lindau, Robert; Andersen, Peter; Wax, Mark K.
Abstract Background Stomal recurrence in patients after laryngectomy has a poor prognosis. Studies performed using sternal resection with pectoralis flap reconstruction report <25% 2‐year survival. The purpose of this study was to ascertain whether the use of larger resection with free flap reconstruction improves survival. Methods Thirteen cases of stomal recurrence that underwent extended sternal resection and free flap reconstruction were identified and classified according to Sisson criteria. Postoperative morbidity, mortality, and survival were assessed. Results Median survival was 10 months in patients with Sisson types I and II, with 37.5% 1‐year and 25% 2‐year survival. Median survival was 6 months in patients with Sisson types III and IV, with 40% 1‐year and 0% 2‐year survival. There were 2 perioperative deaths and a major morbidity rate of 45%. Conclusion Salvage surgery using free flap reconstruction did not show improved survival rates compared with previously described techniques. © 2013 Wiley Periodicals, Inc. Head Neck, 36: 1431–1434, 2014